L’éducation coloniale au prisme de l’intersectionnalité(Antilles françaises, 1795-1830) - Caroline Fayolle (Amnis)
Little historiographical scholarship has been devoted to the schools established in the French West Indian colonies during the revolutionary and post-revolutionary periods. This article sheds light on these historical periods through intersectional analyses that are centered on two main areas. The first addresses racial desegregation and coeducation in the colonial schools ushered in by the Directory following the first abolition of slavery. The second examines the reorganization of the school system after 1802, the year that slavery was reinstated. Examining these schools reveals how systems of discrimination based on gender, race and class interlocked in the colonial societies of the French West Indies at a time when scholars who upheld the status quo questioned the ability of black people and women to excel academically.